Prinsip Persamaan dalam Al-Qur’an dan Implikasinya terhadap Hak Asasi Manusia - Whidy Anastasya; Dzulkifli Hadi Imawan (Getpress Management Journals, 2025)
This research focuses on the concept of equality rights in the perspective of human rights as reflected in the Qur'an. The essence of this research is to examine the importance of the principle of equality in building a plural and civilized social life. This research uses a qualitative method with a library research approach, which relies on analyzing Qur'anic verses related to the issue of equality and human dignity. The results show that Islam, as reflected in the Qur'an, does not differentiate between men and women in terms of human rights. Both sexes are positioned equally as servants of God who have the same honor, responsibilities, and rights in spiritual, social, and moral dimensions. This finding confirms that the Qur'an upholds the principles of justice and equality as the main foundation in respecting human rights.